2013
DOI: 10.5194/bg-10-3221-2013
|View full text |Cite
|
Sign up to set email alerts
|

Sediment transport along the Cap de Creus Canyon flank during a mild, wet winter

Abstract: Cap de Creus Canyon (CCC) is known as a preferential conduit for particulate matter leaving the Gulf of Lion continental shelf towards the slope and the basin, particularly in winter when storms and dense shelf water cascading coalesce to enhance the seaward export of shelf waters. During the CASCADE (CAscading, Storm, Convection, Advection and Downwelling Events) cruise in March 2011, deployments of recording instruments within the canyon and vertical profiling of the water column properties were conducted to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Increased current speeds (up to 0.68 m s −1 ) and SSC (up to 7.37 mg L −1 ) were recorded. The fact that flooding occurred several days after the main pulse of downcanyon sediment transport suggest again, that erosion from the adjacent shelf was the main source of particles introduced in the canyon during mid-March (Martín et al, 2013). The turbid flow did not penetrate into the canyon deeper than about 350 m. The coarsening of the grain size of the particles collected at CC300 suggest that near-bottom currents during this event where strong enough to resuspend and transport coarse particles in suspension from the shelf to the canyon head (Fig.…”
Section: Atmospheric Forcing Of Particle Fluxes In Winter 2010-2011mentioning
confidence: 99%
“…Increased current speeds (up to 0.68 m s −1 ) and SSC (up to 7.37 mg L −1 ) were recorded. The fact that flooding occurred several days after the main pulse of downcanyon sediment transport suggest again, that erosion from the adjacent shelf was the main source of particles introduced in the canyon during mid-March (Martín et al, 2013). The turbid flow did not penetrate into the canyon deeper than about 350 m. The coarsening of the grain size of the particles collected at CC300 suggest that near-bottom currents during this event where strong enough to resuspend and transport coarse particles in suspension from the shelf to the canyon head (Fig.…”
Section: Atmospheric Forcing Of Particle Fluxes In Winter 2010-2011mentioning
confidence: 99%
“…The canyons located on the western part of the GoL (Cap de Creus, hereafter CCC, and Lacaze-Duthiers) play a predominant role in the export of dense coastal waters by guiding them across the continental slope (Canals et al, 2006;Palanques et al, 2008;Puig et al, 2008;Ulses et al, 2008b;Durrieu de Madron et al, 2013;Martín et al, 2013), allowing them to reach great depths in the coldest years. Canals et al (2006) and Ulses et al (2008c) showed that, during the extremely cold winter of 2005, more than two thirds of the GoL shelf waters (∼ 750 km 3 ) were exported to the deep ocean by cascading.…”
Section: Introductionmentioning
confidence: 99%
“…During the mild winter of 2010-2011, only brief, weak cascading was recorded (Rumín-Caparrós et al, 2013). In March, the CASCADE (CAscading, Storm, Convection, Advection and Downwelling Events) experiment documented the hydrological and hydrodynamic characteristics of the south-western GoL shelf and export zone during a period of low loss of buoyancy (Bourrin et al, 2015;Martín et al, 2013). Two intense easterly wind events resulted in coastal currents greater than 0.60 m s −1 over the 26 m deep water column of the south-western GoL shelf (Bourrin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased current speeds (up to 0.68 m s −1 ) and SSC (up to 7.37 mg L −1 ) were recorded. The fact that flooding occurred several days after the main pulse of downcanyon sediment transport suggest again, that erosion from the adjacent shelf was the main source of particles introduced in the canyon during mid-March 2011 (Martín et al, 2013). The turbid flow did not penetrate into the canyon deeper than about 350 m. The coarsening of the grain size of the particles collected at CC300 suggest that near-bottom currents during this event where strong enough to resuspend and transport coarse particles in suspension from the shelf to the canyon head (Fig.…”
Section: Atmospheric Forcing Of Particle Fluxes In Winter 2010-2011mentioning
confidence: 99%